COMPARISON OF NEGATIVE PRESSURE VACUUM THERAPY (NPWT) AND TIE OVER DRESSING IN HEALING SKIN GRAFTS - Farah Naz,; Rana Hassan Javaid ,; Danish Almas,; Yousuf, Bilal Yousuf; Sara Noor,; Aneeq Ahmed Awan, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Negative pressure wound therapy (NPWT) accelerates wound healing by inducing growth factors, evaporating fluid, removing microorganisms, and improving microcirculation. Compared to it the traditional technique involves applying a dressing that is tied over and secured with nylon stitches commonly known as tie over dressing. Both the methods of graft fixing have their pros and cons therefore current study was designed to compare the efficacy of tie over dressing and NPWT methods for securing split thickness skin grafts and sheet grafts. Methods: A randomized control trial was conducted at tertiary care hospital of Karachi from July to December 2023. Participants who visited the department for grafting, fulfilled the inclusion criteria and given consent throughout the study duration were included in the study. The participants were selected by non-probability consecutive sampling technique and groups were allotted by sealed envelope method. Group 1 received tie over dressing and Group 2 received NPWT dressing. The wounds were evaluated after 5 days for tie over dressing and after 3 days for NPWT dressing. Results: The wound were assessed for outcome (healing and complications) after 14 days. The percentage of graft take identified as 11 (31.4%) participants of tie over dressing group and 28 (80%) participants of NPWT dressing material had more than 50% graft take however, remaining participants of both the group suffered the wound healing complications and delayed healing. The significant (p<0.05) differences were observed for graft loss, hematoma formation, and infection. However, 25 (71.4%) participants of Vac-NPWT faced no complication (p-value =0.001). No patient in either group had complete graft loss. Conclusion: NPWT dressing has superiority in preventing graft loss, hematoma formation, and infection over tie over dressing.